Use of crossbred cows for dairy-draught under smallholders farm conditions of Holetta area - Alemayehu, M.; Gebre-Wold, A.; Tegegne, Azage (Ethiopian Agricultural Research Organization, 2002)
Based on the promising results obtained from on-station, the dairy-draught study was further taken to on-farm for testing it under the Ethiopian smallholder farmers' management conditions. The study was undertaken in Holetta and Addis Alem areas between 1993 and 1997. Mean daily milk yield was similar between working (5.08 Kg) and non-working (5.58 Kg) crossbred cows that were kept under smallholder farm management conditions. Lactation yield of non-working cows was significantly higher (2103.57 versus 1725.17 Kg) than that of working cows. This difference emanated from lactation length where non-working cows had exhibited significantly longer lactation length. Mean milk composition of working and non-working cows was similar in fat, protein and total solid contents. Working cows were observed to lose more weight after calving than non-working cows at both onset of first postpartum oestrous and conception though not statistically significant. There were no significant differences between working and non-working crossbred cows in mean intervals of calving to first postpartum oestrous and calving to conception. The interval from first oestrous to conception after second calving was shorter than during first calving where working and non-working cows conceived about 42 and 32 days, respectively, after exhibiting first oestrous. This suggests that postpartum anoestrous was a more important problem than conception failure during the second than the first calving period. In general, the crossbred cows have been in negative energy balance as this was seen from their body weight loss over the most period of the year (after March until the end of October). It has been noticed that the optimum workload that crossbred cows could undertake is satisfactorily comparable to that of local oxen in accomplishing ploughing activity on small farm sizes. It was concluded that as long as improved feeding management and lower level of work are coupled, it is unlikely for traction to have adverse effect on productive and reproductive performances of crossbred dairy cows.